When I feel scared - Spelman, Cornelia; Parkinson, Kathy (Morton Grove, Ill. : Whitman, 2002)
A child describes situations that bring about fear, how it feels to be scared, and what can make things better.
Booklist
1.4
K-3
K-3
Keywords: Fear -- Fiction; Fear -- Fiction